Interaction Design of ITB Library Application Using User-Centered Design - Elisabeth Levana Thedjakusuma; Fetty Fitriyanti Lubis (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2022)
The Technical Implementation Unit is a part of a university or institute that supports the three pillars of higher education, one of which is the library. Library has a large collection of resources that can be accessed through a library catalog. ITB Library is a mobile application that allows users to search catalogs, but it currently lacks optimal appearance and user experience. The aim of this final project is to improve the ITB Library by implementing a user-centered design approach, which focuses on understanding and addressing user needs. The end goal is to create a high-fidelity prototype that meets the usability goals of effective to use, have good utility, easy to learn, and the user experience goal of being helpful. To evaluate the design, usability testing was conducted on the prototype. Testing was evaluated using several metrics, including task completion rate (100%), System Usability Scale (SUS) (93/100), Single Ease Question (SEQ) (6.7/7), and Intrinsic Motivation Inventory (IMI) (6.7/7 for the value/usefulness subscale) during the third iteration. Based on the results of the testing, the interaction design of the ITB Library meets the usability and user experience goals that were set out to be achieved.